On the long-run neutrality of demand shocks - Wenjuan Chen; Aleksei Netsunajev (Humboldt University of Berlin, Collaborative Research Center 649 - Economic Risk, 2015)
Long run neutrality restrictions have been widely used to identify structural shocks in VAR models. This paper revisits the seminal paper by Blanchard and Quah (1989), and investigates their identification scheme. We use structural VAR models with smoothly changing covariances for identification of shocks. The resulted impulse responses are economically meaningful. Formal test results reject the long-run neutrality of demand shocks.
Keywords: C32; 330; smooth transition VAR models; identification via heteroskedasticity; long-run neutrality; aggregate demand; aggregate supply